2013
DOI: 10.1016/j.physbeh.2013.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of locomotor defects in neonatal mice lacking proprioceptive feedback

Abstract: Proprioceptive feedback derived from specialized receptors in skeletal muscle is critical in forming an accurate map of limb position in space, and is used by the central nervous system to plan future movements and to determine accuracy of executed movements. Knockout mouse strains for genes expressed by proprioceptive sensory neurons have been generated that result in generalized motor deficits, but these deficits have not been quantitatively characterized. Here we characterize a conditional knockout mouse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In addition to this hunched posture, DSCAM 2J mice also displayed an aberrant limb hyperkinesia during treadmill locomotion, which likely results from proprioceptive deficits. Limb hyperflexion and hyperextension have been previously reported following peripheral sensory denervation or peripheral deafferentation in the free-walking cat (Bouyer and Rossignol 2003;Bretzner and Drew 2005;Wiesendanger 1964), and upon conditional deletion of proprioceptive DRGs in the neonatal mouse (Dallman and Ladle 2013). Moreover, mutant mouse models lacking muscle spindles also exhibit a similar hyperextension to DSCAM 2J mice (Andrechek et al 2002;Ernfors et al 1994;Klein et al 1994).…”
Section: Functional Postural and Locomotor Implicationsmentioning
confidence: 81%
“…In addition to this hunched posture, DSCAM 2J mice also displayed an aberrant limb hyperkinesia during treadmill locomotion, which likely results from proprioceptive deficits. Limb hyperflexion and hyperextension have been previously reported following peripheral sensory denervation or peripheral deafferentation in the free-walking cat (Bouyer and Rossignol 2003;Bretzner and Drew 2005;Wiesendanger 1964), and upon conditional deletion of proprioceptive DRGs in the neonatal mouse (Dallman and Ladle 2013). Moreover, mutant mouse models lacking muscle spindles also exhibit a similar hyperextension to DSCAM 2J mice (Andrechek et al 2002;Ernfors et al 1994;Klein et al 1994).…”
Section: Functional Postural and Locomotor Implicationsmentioning
confidence: 81%
“…These findings add to a growing body of literature showing that motor behavior, including species‐typical action patterns, expressed by the newborn mammal is modulated by sensory feedback. This includes spontaneous limb activity (Brumley & Robinson, ), locomotor behavior (Brumley et al, ; Dallman & Ladle, ; Viala, Viala, & Fayein, ), facial wiping (Robinson & Smotherman, ; Smotherman & Robinson, ), and righting (Alberts & Ronca, ; Dallman & Ladle, ; Ronca & Alberts, ; Ronca, Fritzsch, Bruce, & Alberts, ; Walton, Harding, Anschel, Harris, & Llinas, ; Wubbels & de Jong, ).…”
Section: Discussionmentioning
confidence: 99%
“…The munc18‐1 conditional knockout mouse is a proprioceptive‐specific knockout model, and these animals lack functional proprioceptive feedback due impaired proprioceptive neuron synaptic transmission. However, it has been suggested that the infant munc18‐1 knockout mouse is able to use cutaneous feedback from the limbs to perform locomotor pivoting behavior, albeit using altered motor and postural strategies compared to controls (Dallman & Ladle, ). Thus, cutaneous stimulation may compensate for the lack of proprioceptive feedback, thus making the contribution of each form of sensory stimulation difficult to disentangle still.…”
Section: Discussionmentioning
confidence: 99%
“…Gait analysis is promising for the evaluation of neurological deficits as gait is a fundamental, physiological and unforced form of locomotion with direct clinical relevance. 3D digital gait analysis could be a useful tool for detecting the severity of neuropathic pain and the change in gait characteristics following SNL [11,[14][15][16][17][18][19][20][21][22][23][24]. Indeed, some authors claim that 2D catwalk analysis is useful for assessing animal pain [9,10,12,13], and these types of measures are relatively easy to assess [13,21].…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous withdrawal reactions are strongly affected by spinal reflex, and scientific evidence that the reactions are a specific reflex against pain is lacking [5]. In addition, the von Frey withdrawal test has some issues of test-retest reliability and interrater reliability [5,[9][10][11][12][13][14]. The test cannot reveal impaired coordination of the motions of the right-left lower limbs in rodent models following SNL or spinal cord injury [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%